2005
DOI: 10.1038/nature03971
|View full text |Cite
|
Sign up to set email alerts
|

Trace element signature of subduction-zone fluids, melts and supercritical liquids at 120–180 km depth

Abstract: Fluids and melts liberated from subducting oceanic crust recycle lithophile elements back into the mantle wedge, facilitate melting and ultimately lead to prolific subduction-zone arc volcanism. The nature and composition of the mobile phases generated in the subducting slab at high pressures have, however, remained largely unknown. Here we report direct LA-ICPMS measurements of the composition of fluids and melts equilibrated with a basaltic eclogite at pressures equivalent to depths in the Earth of 120-180 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
842
3
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,204 publications
(887 citation statements)
references
References 27 publications
33
842
3
9
Order By: Relevance
“…Sr is not carried into the mantle by low-density fluids at T < 900 °C, but is efficiently transported in the higher-T, low-density fluids, melts and high-density fluids, with a partition coefficient of about 20. Schmidt et al (2004) demonstrated that subducted MORB basalts, pelites and greywackes will all develop similar eclogitic mineral assemblages and that the coexisting fluids will be rich in Si and K. Schmidt et al (2004) and Ishikawa et al (2005) both determined that supercritical, solute-rich fluids/melts evolved from the slab would be aqueous and strikingly enriched in B, Ba, Rb and K. It therefore seems likely that the Kessel et al (2005) partitioning relationships will be valid for a wide range of subducted rocks.…”
Section: Origin Of the Crustal Component In The Mafic To Intermediatementioning
confidence: 99%
See 2 more Smart Citations
“…Sr is not carried into the mantle by low-density fluids at T < 900 °C, but is efficiently transported in the higher-T, low-density fluids, melts and high-density fluids, with a partition coefficient of about 20. Schmidt et al (2004) demonstrated that subducted MORB basalts, pelites and greywackes will all develop similar eclogitic mineral assemblages and that the coexisting fluids will be rich in Si and K. Schmidt et al (2004) and Ishikawa et al (2005) both determined that supercritical, solute-rich fluids/melts evolved from the slab would be aqueous and strikingly enriched in B, Ba, Rb and K. It therefore seems likely that the Kessel et al (2005) partitioning relationships will be valid for a wide range of subducted rocks.…”
Section: Origin Of the Crustal Component In The Mafic To Intermediatementioning
confidence: 99%
“…At these great depths the fugitive phase, whether low-density fluid, melt or high-density fluid, would always be highly enriched in Rb and Ba. Fluid/melt-mineral partition coefficients (Kessel et al, 2005) are of the order of 100 and 40 respectively, implying efficient scavenging of these elements from the slab into the mantle. Sr is not carried into the mantle by low-density fluids at T < 900 °C, but is efficiently transported in the higher-T, low-density fluids, melts and high-density fluids, with a partition coefficient of about 20.…”
Section: Origin Of the Crustal Component In The Mafic To Intermediatementioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been proposed that the Nd and Hf isotopic compositions of northern Tonga-southern Kermadec lavas represent pre-existing mantle wedge heterogeneities (for example, refs 12,40,41), the corresponding Sr and Pb isotopic compositions are interpreted as reflecting slab-derived, fluidtransported Sr and Pb from altered oceanic crust and sediment cover into the overlying mantle wedge (for example, refs [42][43][44]. This dichotomy allows us to track slab-derived inputs through the 'subduction factory'.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of volcaniclastic material into the mantle source beneath the central TongaKermadec arc should result in elevated Sr isotope values, which is only observed to a minor extent in lavas from 'U' and 'V'. Pb and Sr each have different mobility in aqueous fluids (for example, refs 43,44) and may, therefore, be decoupled. However, as we observe only a minor increase in Sr, we favour a predominant influence through dehydration of the altered Louisville crust.…”
Section: Resultsmentioning
confidence: 99%